(untitled) (PANGEEA, 2025)
In the context of the current crisis caused by the COVID-19 pandemic, educational institutions have been forced to move towards online education, and the revolution in information and communication technology (ICT) has contributed to the emergence of new and innovative learning methods for students. E-learning provides easier access to learning, promotes flexibility, so that students can overcome the limitations of space and time; it also offers greater potential for the teaching process to focus on the needs and possibilities of learners, focusing on different learning styles.